2022
DOI: 10.3390/ijerph19010555
|View full text |Cite
|
Sign up to set email alerts
|

Direct Access to Physical Therapy: Should Italy Move Forward?

Abstract: Direct access to physical therapy (DAPT) is the patient’s ability to self-refer to a physical therapist, without previous consultation from any other professional. This model of care has been implemented in many healthcare systems since it has demonstrated better outcomes than traditional models of care. The model of DAPT mainly focuses on the management of musculoskeletal disorders, with a huge epidemiological burden and worldwide healthcare systems workload. Among the healthcare professionals, physical thera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 27 publications
0
14
0
1
Order By: Relevance
“…Our results showed that Italian physiotherapists were more focused on the patients’ beliefs and preferences instead of their anxiety surrounding safety, recognizing the patient-centered approach as a key feature of their practice [ 99 ]. Our results also demonstrated that working in a direct access setting and having more years of practice is associated with an increase in comfort level; that is, giving the opportunity to practice their skills increases the physiotherapists’ confidence [ 100 102 ]. In line with UK, USA, and the Netherlands, most respondents perceived “lack of practice/training” and “lack of clinical experience” as major barriers to performing SM for all spinal regions [ 26 28 ].…”
Section: Discussionmentioning
confidence: 88%
“…Our results showed that Italian physiotherapists were more focused on the patients’ beliefs and preferences instead of their anxiety surrounding safety, recognizing the patient-centered approach as a key feature of their practice [ 99 ]. Our results also demonstrated that working in a direct access setting and having more years of practice is associated with an increase in comfort level; that is, giving the opportunity to practice their skills increases the physiotherapists’ confidence [ 100 102 ]. In line with UK, USA, and the Netherlands, most respondents perceived “lack of practice/training” and “lack of clinical experience” as major barriers to performing SM for all spinal regions [ 26 28 ].…”
Section: Discussionmentioning
confidence: 88%
“…Our case report illustrates the informed clinical decision-making process performed by a physiotherapist working in a direct access setting that led to triage a cardiovascular disease in a patient complaining of NP [ 75 , 76 , 77 ]. NP and head/orofacial symptoms have been already observed as the early manifestation of cardiovascular diseases (including PFO), vascular pathologies and blood flow limitations [ 8 , 64 , 65 , 78 , 79 ].…”
Section: Discussionmentioning
confidence: 99%
“…Clinical Practice Guidelines are paramount to implement the most updated available knowledge in clinical practice [45,46]. Additionally, as the Italian Physiotherapy Association advocates for direct access [28][29][30], Clinical Practice Guidelines knowledge is a professional responsibility [47]. Surprisingly, 60.2% reported that cardiovascular measurements are outside their scope of practice.…”
Section: Key Findingsmentioning
confidence: 99%
“…In Italy cardiovascular rehabilitation is included during the entry level training for physiotherapists. Italian physiotherapists are also increasingly practicing as direct access providers, which potentially makes them the first point of contact within the healthcare system [28][29][30]. Therefore, it is imperative that Italian physiotherapists understand the importance of CVD screening, and demonstrate competency impact the patient and the practitioner.…”
Section: Introductionmentioning
confidence: 99%